The Importance of Lipoprotein Lipase Regulation in Atherosclerosis - Anni Kumari (Biomedicines, 2021)
Lipoprotein lipase (LPL) plays a major role in the lipid homeostasis mainly by mediating the intravascular lipolysis of triglyceride rich lipoproteins. Impaired LPL activity leads to the accumulation of chylomicrons and very low-density lipoproteins (VLDL) in plasma, resulting in hypertriglyceridemia. While low-density lipoprotein cholesterol (LDL-C) is recognized as a primary risk factor for atherosclerosis, hypertriglyceridemia has been shown to be an independent risk factor for cardiovascular disease (CVD) and a residual risk factor in atherosclerosis development. In this review, we focus on the lipolysis machinery and discuss the potential role of triglycerides, remnant particles, and lipolysis mediators in the onset and progression of atherosclerotic cardiovascular disease (ASCVD). This review details a number of important factors involved in the maturation and transportation of LPL to the capillaries, where the triglycerides are hydrolyzed, generating remnant lipoproteins. Moreover, LPL and other factors involved in intravascular lipolysis are also reported to impact the clearance of remnant lipoproteins from plasma and promote lipoprotein retention in capillaries. Apolipoproteins (Apo) and angiopoietin-like proteins (ANGPTLs) play a crucial role in regulating LPL activity and recent insights into LPL regulation may elucidate new pharmacological means to address the challenge of hypertriglyceridemia in atherosclerosis development.